2009
DOI: 10.3138/jcs.43.2.220
|View full text |Cite
|
Sign up to set email alerts
|

Inuit Cyberspace: The Struggle for Access for Inuit Qaujimajatuqangit

Abstract: In the field of cyberspace studies, there has been growing interest in researching the implications of cyberspace on ethnic representations and relations, a subject of particular importance for increasingly diverse societies such as Canada. In this essay, the authors examine the relationship between Internet-based new media technologies, the preservation and promotion of Inuit knowledge, and the evolution of Canada’s national identity. The authors examine whether new media technologies can serve as a means to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 15 publications
2
21
0
1
Order By: Relevance
“…It was conducted over a short time frame (three and a half months) that only allowed for a general survey and a snapshot of some current projects. Despite these limits, it supported previous research demonstrating a widespread lack of broadband infrastructure and robust connectivity services in many rural and remote First Nations communities (Alexander, 2001(Alexander, , 2009Fiser, 2010;O'Donnell et al, 2010;Walmark, O'Donnell, & Beaton, 2005). It also supported previous findings that many First Nations are engaged in a range of innovative, community-driven broadband and ICT development projects.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…It was conducted over a short time frame (three and a half months) that only allowed for a general survey and a snapshot of some current projects. Despite these limits, it supported previous research demonstrating a widespread lack of broadband infrastructure and robust connectivity services in many rural and remote First Nations communities (Alexander, 2001(Alexander, , 2009Fiser, 2010;O'Donnell et al, 2010;Walmark, O'Donnell, & Beaton, 2005). It also supported previous findings that many First Nations are engaged in a range of innovative, community-driven broadband and ICT development projects.…”
supporting
confidence: 60%
“…For rural and remote First Nations, these policy challenges, and efforts to address them, must be accompanied with specific considerations that relate to their unique status as self-governing Aboriginal nations (Alexander, 2009;Fiser & Seibel, 2009;McMahon et al, 2010). First Nations have long argued that centralized government programs and policies preclude the efforts of their own Aboriginal governments to secure self-determination.…”
Section: Digital Divides and First Nations In Canadamentioning
confidence: 99%
“…Broadband infrastructure can be framed as a component of indigenous self-determination (Mignone & Henley, 2009). the general consensus among government, academics, and industry commentators is that broadband infrastructure plays an important role in community development (see, for example, Alexander, Adamson, Daborn, Houston, & tootoo, 2009). Benkler writes that "high capacity networks are seen as strategic infrastructure, intended to contribute to high and sustainable economic growth and to core aspects of human development" (Benkler, 2010, p. 11;see also Matear, 2002;o'Donnell et al, 2010a).…”
Section: "Digital Self-determination" and Indigenous Community Develomentioning
confidence: 99%
“…Of greater interest are the opportunities it currently provides Inuit young people for creatively mediating social relationships and historical consciousness. Recent scholarship on Inuit use of cyberspace (Alexander et al 2009;Christensen 2003;Hot 2010) calls attention to these opportunities and to the fluid connections forged online and offline. Indeed, in our examination of these video snippets of everyday life in the North, and of the dialogue posted in the comment section, we found that most of the input was from family or friends.…”
Section: Digital Networking and Social Imaginationsmentioning
confidence: 99%
“…Yet this act of connecting, expressing, creating, recording, and broadcasting oneself on video-sharing sites-what Wesch (2008) calls "YouTubing" oneself-has become increasingly common in Arctic communities. Since the 2005-2007 expansion of broadband Internet access via satellite into remote communities in the Canadian Arctic (Alexander et al 2009;Hot 2010) and the more recent, transnational growth of social networking sites and video-sharing technology (Qualman 2009;Wesch 2008), the digitising and uploading of experience has become part of the "practice of everyday life" (de Certeau 1984) in the Canadian North. Geographically diffuse Inuit young people now create online spaces to post short excerpts from their lives and connect with others (Hot 2010) 3 .…”
Section: Résumé De L'articlementioning
confidence: 99%